2019
DOI: 10.1016/j.ijnurstu.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of expatriate nurses providing end of life care to Muslim patients in a Muslim country: An integrated review of the literature

Abstract: Background: The provision of appropriate end of life care for patients who have different life experiences, beliefs, value systems, religions, languages, and notions of healthcare, can be difficult and stressful for the nurse. To date, research has focused predominately on nurses' experiences of end of life care for the Muslim patient who is an immigrant in another country. Objectives: To critically review the literature related to the lived experiences of non-Muslim expatriate nurses providing end of life car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Outcomes: The outcomes of this review included the family research methods, sample, research instruments used and common themes across these studies. The search focussed on research during cancer treatment [within first year] but excluded end of life as much research is on managing supportive care for the person with cancer rather than the family as unit of care (Oakley et al, 2019). (Bell, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Outcomes: The outcomes of this review included the family research methods, sample, research instruments used and common themes across these studies. The search focussed on research during cancer treatment [within first year] but excluded end of life as much research is on managing supportive care for the person with cancer rather than the family as unit of care (Oakley et al, 2019). (Bell, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In a study, nurses acknowledged the importance of language when caring for patients, and it was significantly associated with rendering proper care. Although nursing education in Saudi Arabia has gone through significant developments, it is still a profession with societal and cultural stigmas (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al's (2018) reported similar findings with nurses working in Singapore needing to learn more about the patients' cultures and beliefs to support their spiritual needs at end-of-life. An integrative review highlighted that international nurses working in Middle Eastern Muslim countries may not fully understand the nuances of local customs and beliefs surrounding death and dying, potentially impacting the delivery of culturally appropriate end-of-life care (Oakley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%